Relationship of nicotine deprivation and indices of alcohol use behavior to implicit alcohol and cigarette approach cognitions in smokers. (April 2017) - Cohn, Amy; Ehlke, Sarah; Cobb, Caroline O.
Abstract: Alcohol and smoking frequently co-occur and alcohol is a primary trigger for smoking behavior and relapse back to smoking. This study examined whether several indices of alcohol use behavior and consequences of use would be associated with changes in implicit alcohol-approach versus implicit cigarette-approach cognitions under cigarette deprived and non-deprived cognitions in 109 smokers who drank at risky or non-risky levels. An Implicit Association Task (IAT) measured how quickly respondents paired alcohol and cigarette pictures with approach and avoid words. Regression analyses examined the associations of quantity/frequency, proportion heavy drinking days, number of DSM-IV alcohol use disorder (AUD) symptoms, and risky drinking status to IAT scores under deprived conditions, controlling for IAT order effects, non-deprived IAT score, and deprived cigarette craving and withdrawal. Interactions with craving and withdrawal intensity were also examined. Results showed a significant positive association between proportion of heavy drinking days and stronger alcohol-approach than cigarette-approach motivations when deprived. There was also a conditional association of AUD symptoms to alcohol-approach motivations among respondents reporting more intense withdrawal when deprived. Alcohol quantity and frequency, as well as risky drinking status were unrelated to change in IAT scores. Findings suggest that cigarette deprivation may magnify motivation to drink, rather than smoke, among smokers who engage in more frequent bouts of heavy drinking and who report more alcohol-related problems. Results also show relative momentary and unconscious "preference" or choice for alcohol over cigarettes in some high-risk smokers, when cigarette craving and withdrawal are high. Highlights: Problem drinking smokers had stronger implicit alcohol than cigarette motivations. Motivations toward drinking and smoking differed under cigarette deprivation for sub-groups of smokers. Withdrawal intensity impacted associations between AUD symptoms and implicit cognitions. Cessation treatments should target drinking cognitions in smokers who drink heavily and have more alcohol-related problems.